HUBUNGAN GAYA HIDUP DENGAN PENYAKIT HIPERTENSI PADA PASIEN RAWAT INAP DI RSUD HAJI MAKASSAR - Nursyamsiyah Nursyamsiyah; Nur Qamariyah (Pusat Riset dan Inovasi Nasional, 2021)
Lifestyle is an important factor that influences people's lives. This research method uses descriptive analytics with a cross sectional approach. The total population in this study was all patients who experienced hypertension at the Haji Makassar Regional General Hospital, totaling 316 people. In this research, the sample used was purposive sampling. The sample in this study was 47 patients who experienced hypertension at the Haji Makassar Regional General Hospital. The instruments used in this research were questionnaires and observations. The research results obtained a value of ρ=0.008<0.05, this means that there is a relationship between diet and hypertension in inpatients at the Haji Makassar District Hospital. Based on the results of data analysis, it was obtained that the value ρ=0.003<0.05 means that there is a relationship between smoking and hypertension in inpatients at the Haji Makassar Regional Hospital. This research is used as input for health workers who carry out their duties in providing nursing care, especially in cases of hypertension.